PERENCANAAN BENDUNGAN BENDO PONOROGO - Rahmawanto Fajar; Ahmad Busiri; Sri Sangkawati; Hary Budieny (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
A number of regions in Ponorogo, East Java Province has a variety of water resource management issues, including floods during the rainy season and water short ages during the dry season. To overcome these problems then we planned Bendo dam. Methods of planning begins with determining the position of the location, hydrology and hydraulics which finally obtained information to determine the design of the dam. Bendo dam is planned to use dependable discharge with a probability of 80%. Water requirement value to fulfill the needs of irrigation water is 2.19 liters/sec/hectare and the water requirement is 823.7 liter/sec. We used HSS Nakayasu Flood discharge method with 1,000-year return period amounted to 676.37 m3 / sec. Bendo dam is also planned as a hydropower that produces 1.697,953 Kw hydroelectric power. Bendo dam is planned using Rockfill dam type with a core of impermeable clay with a slope of 1: 2,5 in the upstream and 1: 1,75 in the downstream. The peak height is 78,5 m, the width of the peak is 13 m, and the full length of the dam is 354,02 m with 50-years lifetime design.